2021
DOI: 10.1021/acs.jpcb.1c06019
|View full text |Cite
|
Sign up to set email alerts
|

Tau Protein Binding Modes in Alzheimer’s Disease for Cationic Luminescent Ligands

Abstract: The bi-thiophene-vinylene-benzothiazole (bTVBT4) ligand developed for Alzheimer’s disease (AD)-specific detection of amyloid tau has been studied by a combination of several theoretical methods and experimental spectroscopies. With reference to the cryo-EM tau structure of the tau protofilament ( 28678775 Nature 2017 547 185 ), a periodic model system of the fibril was created, and the interactions between this fibril and bTVBT4 were studied with nonbiased m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 39 publications
3
25
0
Order By: Relevance
“…Hence, properly functionalized proteophenes might offer the possibility to detect specific types of protein aggregates, and the recently obtained cryo‐EM structures of a diversity of protein aggregates[ 34 , 35 , 36 , 37 , 38 , 44 , 45 , 46 ] might aid in assigning distinct binding mode for different ligands. As recently shown, [47] combinatorial experimental/theoretical assessment could be utilized to predict the binding mode, as well as photophysical characteristics, of an AD‐tau‐specific thiophene‐based ligand, b‐TVBT4, and similar studies with proteophenes are ongoing in our laboratory to determine their binding modes to different protein aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, properly functionalized proteophenes might offer the possibility to detect specific types of protein aggregates, and the recently obtained cryo‐EM structures of a diversity of protein aggregates[ 34 , 35 , 36 , 37 , 38 , 44 , 45 , 46 ] might aid in assigning distinct binding mode for different ligands. As recently shown, [47] combinatorial experimental/theoretical assessment could be utilized to predict the binding mode, as well as photophysical characteristics, of an AD‐tau‐specific thiophene‐based ligand, b‐TVBT4, and similar studies with proteophenes are ongoing in our laboratory to determine their binding modes to different protein aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…While second-generation PET tracers have been developed to reduce off-target binding and optimize pharmacokinetic properties ( 22, 23 ), their direct binding to disease-relevant tau filament folds is undercharacterized. Docking studies have predicted that PET tracers bind end-to-end with the plane of the aromatic rings parallel to the fibril axis ( 24, 25 ), and a cryo-EM structure of the PET tracer APN-1607 at low-resolution ( 26 ) has been modeled to have the same orientation. On the other hand, cryo-EM studies of the small molecule Epigallocatechin gallate (EGCG, a compound known to disaggregate amyloid filaments in vitro ) ( 27 ) bound to AD tau PHFs showed several unique densities.…”
Section: Main Textmentioning
confidence: 99%
“…Filaments present a unique challenge for small-molecule design because their accessible surfaces tend to be relatively flat. This limits the amount of surface area potentially lost upon binding of a monomeric small molecule, hence the propensity for docking studies to show face-on binding of flat small molecules to the amyloid ( 24, 25 ). However, modeling of EGCG bound to one of the sites in tau PHFs by Eisenberg and colleagues indicates a similar ligand orientation to our tau PHF:GTP-1 model, in which the rings lie perpendicular to and match the symmetry of the fibril ( 28 ).…”
Section: Main Textmentioning
confidence: 99%
“…Through our experimental study, we demonstrated that the E264G mutation (R1R3-GG) favors fibril formation, whereas the G326E mutation (R1R3-EE) forms disordered aggregates. Understanding the conformations of 3R isoforms could pave way to tune PiD specific ligands, which might help in the detection of Tau conformations similar to bithiophene-vinylene-benzothiazole (bTVBT4), which can detect the AD fold but not the PiD fold. With Tau pathogenesis suggested to occur on the surface of MT, the results described in this work share insights on the sequence-specific conformation of Tau protein paving the way to probe pathogenesis at a monomeric level. , Thus, our study exemplifies the importance of NH6 peptides, owing to their ability to tune the conformational properties of the PGGG motif and thus influence the VQ6 peptide downstream to it. The NH6 peptide also plays a significant role in understanding Tau–MT interactions, which might help in building therapeutics targeting the inter-repeat regions.…”
Section: Discussionmentioning
confidence: 58%